Why does Oncotype DX recurrence score reduce adjuvant chemotherapy use? - Schneider, Jeffrey G. (Breast Cancer Res Treat, 2012)
The Oncotype DX recurrence score (RS) reduces breast cancer adjuvant treatment utilization, but the reasons for this effect are not straightforward. We performed a retrospective chart review of 89 consecutive node-negative breast cancer patients for whom RS was ordered to facilitate adjuvant treatment decisions. By subtracting the relapse rate predicted by RS from that calculated using the Adjuvant! Online (AOL) web-based instrument, a “prognostic delta” (PΔ) was determined, reflecting the difference between prognoses predicted by these two indices. Clinician interviews were conducted to evaluate the actual effect of RS on treatment decisions and its relation to PΔ. Adjuvant chemotherapy use decreased from 61 to 26 % as a consequence of RS results (p < 0.0001). In multivariate analysis, RS was the only factor significantly associated with the final adjuvant treatment choice. Surprisingly, RS caused chemotherapy to be withheld even when PΔ was negative (i.e., cases in which RS predicted a less favorable outcome than AOL). The prognostic and chemotherapy predictive utilities of the RS do not fully account for its effect in reducing adjuvant chemotherapy use. Further studies are required to more fully elucidate other factors that may be responsible for this effect, including the possibility of unintended influence.